Humanities in Kazakhstan: development, challenges and characteristics - Zhakin, S.M. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2026)
Modern Kazakhstan has become a kind of testing ground for various experiments in all spheres of public and state life. This is explained by the progressive policies pursued by the country’s current leadership. Despite its autonomy and independence, Kazakhstan cannot help but be involved in the general global process, in the general dynamic space. And the problems that arise in one sphere or another directly or indirectly affect Kazakhstan. In Kazakhstan, the influence of crisis moments in modern humanities in the fields of science, education and public life is felt. In this article, the author attempts to analyse the general state of humanities knowledge in Kazakhstan and, as far as possible, to identify the most important and promising directions in the process of overcoming the crisis in the humanities. The author draws particular attention to the fact that this crisis is especially acute in the fields of education and science. In this sense, the humanities have been relegated to the sidelines of the educational process. Today’s attitudes mainly prioritise natural science and applied research. The humanities have become merely an afterthought in the research sphere. In the article, the author assesses the extent of the problems in the humanities and provides a fundamental evaluation of this phenomenon.
Қазақстандағы гуманитарлық білім: дамуы, мәселелері және ерекшеліктері
Гуманитарное знание в Казахстане: развитие, проблемы и особенности
Keywords: humanitarian sphere; culture; reforms; education; science; reform; crisis; values